Oral approach-avoidance: a replication and extension for European Portuguese phonation - Godinho, S (2016)
Previous research revealed that mouth movements influence attitudes. Covert subvocal articulations inducing muscular contractions resembling ingestion movements were preferred over expectoration-like movements, unveiling a relationship between vocal muscles' wandering and motivational states such as approach and avoidance. These findings, explained in terms of embodied cognition, suggest that specific movements are directly connected to, and more importantly, automatically activate concordant motivational states. The oral approach-avoidance effect was replicated using the original stimulus set and a new set of stimulus developed for Portuguese. Results from two high-powered (total N?=?407), independent replications, revealed that the preference for inward words (over outwards) exists in both sets but to a greater extent in the pool phonetically adapted for Portuguese.